“Plan de marketing para la empresa Meta Bikes ubicada el cantón Yantzaza, provincia de Zamora Chinchipe, periodo 2024-2026” - Merino Salinas, Yesly Jalil (2024)
The present research develops a marketing plan aimed at the company Meta Bikes, located in the canton of Yantzaza, Zamora Chinchipe province, with the objective of strengthening its positioning, competitiveness, and increasing its market share during the 2024-2026 period by attracting and retaining customers interested in cycling and sustainable mobility. The study seeks to improve Meta Bikes’ visibility and reach in a highly competitive region that lacks specialized offerings in cycling products and services. The research is based on a descriptive and exploratory methodology, utilizing both qualitative and quantitative techniques. A comprehensive analysis of internal and external factors is conducted using tools such as the SWOT analysis, which identifies the company’s strengths, weaknesses, opportunities, and threats. Among the most relevant findings, there is evidence of a growing regional demand for bicycles and maintenance services, as well as a strong consumer preference for high-quality brands, specialized technical services, and affordable products and spare parts. The marketing plan is structured around the marketing mix model, encompassing strategies for product, price, place, and promotion adapted to local conditions. Additionally, the plan highlights the importance of establishing strategic partnerships and enhancing both formal and informal advertising presence within the area and on social media to attract new customers and consolidate the loyalty of existing ones. Implementing this plan will enable Meta Bikes to improve its competitive position and expand its market share in the region.